2011
DOI: 10.1177/0022466911419516
|View full text |Cite
|
Sign up to set email alerts
|

Intervention Fidelity in Special and General Education Research Journals

Abstract: Treatment fidelity reporting practices are described for journals that published general and special education intervention research with high impact factors from 2005 through 2009. The authors reviewed research articles, reported the proportion of intervention studies that described fidelity measurement, detailed the components of fidelity measurement reported, and determined whether the components of fidelity reported differed based on the research design, the type of intervention, or the number of intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
106
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 13 publications
6
106
0
Order By: Relevance
“…As this study showed, it is not easy to implement an intervention in kindergarten to enhance differentiation for high-ability children. It is thus important to take the following learned lessons into account in future interventions (Swanson et al 2013). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As this study showed, it is not easy to implement an intervention in kindergarten to enhance differentiation for high-ability children. It is thus important to take the following learned lessons into account in future interventions (Swanson et al 2013). …”
Section: Discussionmentioning
confidence: 99%
“…In this respect, intervention fidelity refers to the implementation of an intervention as intended or designed (O'Donnell 2008). It is important to elucidate the degree of intervention fidelity and which factors affect it (Bywater and Sharples 2012;McKenna, Flower, and Ciullo 2014;O'Donnell 2008;Swanson et al 2013); only then can the relative strength of an intervention for outcomes be assessed and the information used -if necessary -to create a more successful intervention and, finally, to upscale the intervention (Darrow 2013;Swanson et al 2013). Further, as evidence-based interventions that 'can be implemented with fidelity' (Swanson et al 2013, 3) gain attention (Onderwijsraad 2006), it is important that intervention fidelity and factors affecting it are investigated.…”
mentioning
confidence: 99%
“…Though a few recent studies have developed fidelity assessment tools based on a self-reported measure of behavioral health provider fidelity [45] or expert ratings for delivering a complex intervention for chronic pain [46] and a practice change intervention [47] (both of the latter instruments assessed face validity and reliability only), the dearth of validated and published instruments extends beyond weight loss interventions and is well-recognized [48,49,9,[50][51][52][53]. Clearly, there is a need for validated measures to help determine the effectiveness of weight loss interventions when delivered as they were intended.…”
Section: Original Research Discussionmentioning
confidence: 99%
“…The ultimate goal was to enhance the learning and development of all children, including the high-ability children. But before checking student outcomes, it is important to assess the intervention fidelity and actual changes in teacher DP (O'Donnell 2008;Swanson et al 2013). Whether the intervention succeeded in improving teachers' DP by using a designbased research approach (Anderson and Shattuck 2012;Barab and Squire 2004) is the focus of this article.…”
Section: Introductionmentioning
confidence: 99%